Exploring first-feeding diets for European eel larval culture: Insights at morphological, nutritional, and molecular levels. - Elisa Benini; Kasun A Bandara; Sebastian Nikitas Politis; Sofia Engrola; Anders Nielsen; Luis E C Conceição; Andre Santos; Sune Riis Sørensen; Jonna Tomkiewicz (PLoS ONE, 2023)
Closing the life cycle of European eel (Anguilla anguilla) in captivity is targeted to provide a sustainable, year-round supply of juveniles for aquaculture. Present focus is on the nutritional requirements during the larval first-feeding period. In this study, three experimental diets were tested on hatchery-produced European eel larvae from the onset of the first-feeding stage commencing 10 days post hatch (dph) until 28 dph. Larval mortality was recorded daily, while sampling was conducted at regular intervals to record larval biometrics and analyze the expression of genes related to digestion, appetite, feed intake and growth. Two periods of high mortality were identified: the first appeared shortly after introduction of feeds (10-12 dph), while the second occurred 20-24 dph, indicating the "point of no return". This interpretation was supported at the molecular level by the expression of the gene encoding the "hunger hormone" ghrelin (ghrl) that peaked at 22 dph in all dietary trials, suggesting that most larvae were fasting. However, in larvae fed diet 3, ghrl expression was downregulated beyond 22 dph, which indicated that those larvae were no longer starving at this stage, while upregulation of genes encoding the major digestive enzymes (try, tgl, and amyl2a) advocated their healthy development. Moreover, for larvae fed diet 3, the expression of those genes as well as genes for feed intake (pomca) and growth (gh) continued to increase towards 28 dph. These results together with the registered highest survival, largest dry weight increase, and enhanced biometrics (length and body area) pointed to diet 3 as the best-performing. As a whole, this first-feeding study represents a landmark being the first to document European eel larval growth and survival beyond the point of no return, providing novel insights into the molecular development of digestive functions during the first feeding stage.